Project Personnel's Perception on Watershed Development Activities under National Watershed Development Projects for Rainfed Area (NWDPRA) - Purushottam,; Jha, S.K.; Singh, Baldeo (Indian Journal of Extension Education, 2012)
Project personnel under National Watershed Development Projects for Rainfed Area (NWDPRA) were selected to study the perception on relatively important watershed activities and involvement in watershed projects. The majority (67.0 %) of project personnel were Graduate followed by Masters (21.0 %) and Doctorate degree (12.0 %), indicating that the staff was adequately qualified. It was found that the project personnel perceived conservation and production measures (115) more importantly over socio-economic and management aspects (77) for the success of watershed project. It was further observed that these personnel were not much clear to their task in watershed development. The overall 21 activities of their involvement in watershed projects were identified. The involvement of them in socio-economic and management aspects (65) was higher over resource conservation and production measures (47). Than total multiple responses of them were higher (192) under relatively important watershed activities over their involvement in watershed activities (112). Indicates significant gaps between the perceived activities and performed activities under the watershed projects. Further, the responses of project personnel on effectiveness of training in watershed indicated that majority (77.14 %) desired for practical and problem-solving training based on local experiences and training programmes to be organized at the village (55.71%), watershed (31.42 %) and district levels (21.12 %).
Keywords: Project personnel; Perception; Training; , Watershed project